Visible Light Induced Aerobic Coupling of Arylboronic Acids Promoted by Hydrazone. Issue 5 (3rd February 2022) - Xia, Hongyu; Wang, Ganghu; Zhao, Dongbo; Zhu, Chunyin
Abstract: A visible‐light‐induced oxidative coupling of arylboronic acids has been developed for the synthesis of biaryls. The reaction that employs polydentate hydrazones as the bifunctional catalyst works smoothly under room temperature. It is compatible with a wide range of functional group. The study of UV‐Vis spectrum indicated that hydrazone and its complex with CuI show major absorptions upon visible‐light, which secures the dual role of hydrazone as both ligand and photocatalyst in this reaction. Hence, the reaction is proposed to involve stepwise transmetallations, photo‐induced oxidations, and reductive elimination. Abstract :